THE LEVELS OF LEMBANG FAULT ACTIVITY BASED ON GEOMORPHIC INDEXES ON AROUND THE CIKAPUNDUNG WATERSHED, WEST JAVA - Syalsabilla, Lola Lintang; Haryanto, Iyan; Sukiyah, Emi (Journal of Geological Sciences and Applied Geology, 2020)
Lembang Fault is a fault in the highlands of Bandung, which has an East-West direction with a length of about 29 km. This fault greatly affects the landscape around the Cikapundung watershed, especially in the upstream. An analysis performed using the geomorphic index; Basin Shape, Mount Front Sinuosity, Asymmetry Factor, T – Index, Ratio of Valley Floor Width to Valley Height, and Relative Tectonic Activity. Based on the analysis using methods above, the level of tectonic in the Cikapundung watershed ranges from active to low. The presence of Lembang fault affects landscape, forming zone that borders the Bandung highlands and the Subang area in the north.